2010
DOI: 10.1227/01.neu.0000382965.95819.73
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation for Central Poststroke Pain

Abstract: SCS may provide improved pain control in a group of patients with intractable CPSP and may have therapeutic potential for intractable CPSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 21 publications
1
33
0
1
Order By: Relevance
“…Several recent studies have shown HF-SCS to be superior to traditional low-frequency SCS systems (typically delivered at 50 Hz), which was sustained at 12 months and 24 months (3). A couple of case series published within the last decade have also shown effectiveness of traditional SCS in CPSP (4,5). We describe the first reported case of medically refractory CPSP treated with HF-SCS delivered at 10-kHz.…”
Section: To the Editormentioning
confidence: 79%
See 1 more Smart Citation
“…Several recent studies have shown HF-SCS to be superior to traditional low-frequency SCS systems (typically delivered at 50 Hz), which was sustained at 12 months and 24 months (3). A couple of case series published within the last decade have also shown effectiveness of traditional SCS in CPSP (4,5). We describe the first reported case of medically refractory CPSP treated with HF-SCS delivered at 10-kHz.…”
Section: To the Editormentioning
confidence: 79%
“…The tricyclic antidepressant amitriptyline is considered first-line therapy for CPSP and was shown effective in a three-phase crossover study in which carbamazepine was no more effective than placebo. Its use, however, is often limited due to intolerable anticholinergic side-effects (5). The anticonvulsant lamotrigine was found to be moderately effective and well tolerated in a randomized, double-blind study of 30 patients.…”
Section: Discussionmentioning
confidence: 98%
“…SCS has not been recommended for the treatment of CPSP , and not many studies have shown its effect in this context . However, Aly et al reported that over 30% pain reduction determined using VAS was observed in 15 (50%) of 30 CPSP patients during the test SCS, and 7 (77.8%) of 9 patients showed long‐term pain reduction by chronic SCS. Tanei et al reported that 6 (75%) of 8 patients obtained over 50% pain reduction during the test SCS, and this reduction continued for about 12 months in 5 (83%) of 6 patients with chronic SCS.…”
Section: Discussionmentioning
confidence: 99%
“…For peripheral neuropathic pain, SCS has proven to be effective in relieving pain [4–8]. For thalamic pain (central neuropathic pain), the analgesic effect of SCS used to be uncertain; however, two recent studies showed its effectiveness in patients with central neuropathic pain [9, 10]. Lopez et al reported that pain relief was satisfactory in 6 of 8 patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…Lopez et al reported that pain relief was satisfactory in 6 of 8 patients [10]. Aly et al reported that half of the 30 patients experienced good or fair pain relief during the SCS trial [9]. …”
Section: Introductionmentioning
confidence: 99%